Diseño para la construcción de un lepidoptarío al interior del parque ecológico y recreacional “arq. sixto durán ballén” de la ciudad de Santa Elena, provincia de santa elena - Salinas González, María Susana (2009)
This Project proposes to enhance the tourist - environmental demand of the Recreational and Ecological Park “Arq. Sixto Durán Ballén”, located in Santa Elena city, Santa Elena Province, by means a construction of a butterfly’s farm, contributing to its environmental objectives. It also proposes preventive and corrective maintenance of the current facilities, optimization of quality of existing services and management, to increase commercial institutional positioning and its self - sustainability. In the butterfly’s farm, through living experience assisted by specialized Guide, visitors will have the opportunity to enjoy learning the metamorphosis of Lepidoptera, the complex processes of nature and interrelation of diverse components of it, including the people; understanding his important role in the ecological balance. The document provides a general description of the project, including resources and current condition of the Park